(untitled) (Indonesian Tourism Justice Review, 2024)
Indigenous communities in Indonesia face numerous challenges in the context of tourism development, particularly when it comes to protecting their rights, land, and cultural heritage. This paper explores the intersection of indigenous rights and tourism development in Indonesia, with a specific focus on how indigenous communities navigate and engage with tourism projects. Using case studies from regions such as Papua and the Dayak communities in Borneo, the paper examines how tourism can either empower or exploit indigenous groups, depending on how development projects are planned and executed. The research highlights the role of indigenous knowledge, land rights, and cultural heritage in shaping tourism development that respects the rights and autonomy of local populations. The paper discusses legal frameworks that support or fail to protect indigenous rights, including land tenure laws, cultural preservation policies, and the challenges of enforcing these protections in the face of growing tourism demand. It also explores the potential for community-based tourism models that allow indigenous people to benefit from tourism while maintaining control over their land and cultural practices. The paper concludes by offering recommendations for inclusive and justice-oriented tourism development that prioritizes indigenous rights.